Assessment of serotonin precursors and selective serotonin reuptake inhibitor (SSRI) in reducing cannibalistic behavior among hybrid grouper (Epinephelus lanceolatus ♂) x (E. fuscoguttatus♀) juvenile - Sansudin, Nurul Farhana; Nawi, Mohd Firdaus; Mustafa, Sufian (2022)
Cannibalism is a predatory feeding action that involves killing and eating individuals of the same species. The phenomena seem serious in grouper hatchery, especially at the nursery stage. Experiment was designed to assess the effect of serotonin to reduce occurrences of cannibalism. Hence, the study was conducted to evaluate the serotonin precursors and serotonin reuptake inhibitor through fluoxetine, tryptophan and glycine. Juvenile hybrid groupers were divided into six treatment groups with duplicates. Group 1 receive fluoxetine treatment, Group 2 - tryptophan, Group 3 - glycine, Group 4 - fluoxetine + tryptophan, Group 5 - fluoxetine + glycine, while Group 6 will be a negative control. The data taken for analysis included survival rate (SR), feed conversion ratio (FCR) and specific growth rate (SGR). Several samples of blood serum were taken from hybrid grouper juvenile for the quantification of serotonin level by using serotonin ELISA kit. Results from the present experiment showed that tryptophan supplemented diet (1%) significantly (p<0.05) increased the survival rate of hybrid grouper juvenile from 20.50% in the control group to 47% in tryptophan without affecting the growth performance. Other treatments, only showed a slight increase in survival as compared to the control group but not statistically significant (p<0.05). Group 3 supplemented with 1% glycine showed an increment in serotonin level and survival rate but not significant. The two tryptophan-supplemented groups, Group 2 and 4 showed a high serotonin concentration as compared to others. Mix treatment group did not show any significant increase in the serotonin level and also the survival rate of hybrid grouper juvenile. Based on the results of the study, a diet supplemented with 1% tryptophan can increase the serotonin level in the blood serum of hybrid grouper juvenile and subsequently result in a better survival rate.